Methodology for teaching water management activities of the Saryshiganak dam located on the Syrdarya River - Kasabekov Махмұт; Baimbetova Гүлсім; Zhumadilova Анар (Рroblems of engineering and professional education, 2024)
The scientific work considers one of the alternative options for the development of the ecologically unstable Aral Sea region within the framework of the project for the preservation of the small island and the regulation of the Syrdarya riverbed, which provides for a comprehensive acceleration of water management measures on the Small Island and in the lower reaches of the Syrdarya River to stabilize the ecological situation in the region.